On Killing Magnetic Curves in the Hyperboloid Model of $\widetilde{SL}(2,\mathbb{R})$ Geometry - Bosak, Mihaela; Erjavec, Zlatko; Klemenčić, Damjan (Sarajevo Journal of Mathematics, 2025)
A Killing magnetic curve is a trajectory of a charged particle on a Riemannian manifold under the action of a Killing magnetic field. In this paper we study Killing magnetic curves in the hyperboloid model of $\widetilde{SL}(2,\mathbb{R})$ geometry.